Ovarian Strumal Carcinoid Producing Peptide YY Associated With Severe Constipation: A Case Report and Review of the Literature. (January 2015) - Muller, Kristen E.; Tafe, Laura J.; Gonzalez, Jorge L.; West, Loyd A.; Schned, Alan R.
Abstract : Primary carcinoid tumors are rare neoplasms of the ovary. Of the 4 histologic subtypes, ovarian carcinoid tumors with insular patterns produce carcinoid syndrome in approximately one third of cases, versus strumal and trabecular carcinoids which very rarely cause typical carcinoid syndrome. A unique presentation of ovarian carcinoid tumors with concurrent severe constipation has been reported, which is thought to represent a new carcinoid syndrome. The proposed mechanism is the production of peptide YY by the tumor, a gastrointestinal hormone responsible for decreasing gut motility. We report a case of a 34-yr-old white woman who presented with constipation and weight loss for 1 yr, and was found to have a unilateral ovarian strumal carcinoid, which produced peptide YY as demonstrated by immunohistochemistry. The 13 previous case reports of ovarian carcinoids with constipation are reviewed and the clinicopathologic features are discussed. This report and literature review further solidifies this entity as a new type of carcinoid syndrome.